QIRABOX: Quran Murottal Speaker with Speech Recognition Based on Internet of Things - Rimadana, Heny (Faculty of Engineering, Universitas Tanjungpura, 2025)
This research aims to design and implement an IoT-based speaker control system for Quran Murottal using voice commands, specifically targeting visually impaired individuals. The system utilizes speech recognition technology to overcome the challenges that visually impaired users face when controlling devices through buttons or remotes. The Android application